Reproductive efficiency of Egyptian buffalo bulls raised under farmers conditions - KASCHAB, S EL (The Indian Journal of Animal Sciences, 2013)
The present study is a close survey and information recording on the reproductive activities of buffalo bulls owned by peasants in two Districts of El Gharbiya Province under their panicular economic and environmental conditions.The distribution of buffalo bulls and cows was studied. The breeding ratio varied widely betweenvillages and rapged between 0 and 2.78 bulls/100 cows (>2 years old). Bulls arc geographically distributed by chance without any consideration for hreeding ratio and/or distances between the villages. The overall mean of age for bulls studied was 3.8Â±1.5 years and ranged between 16 months and 8.0 years. Some body measurements of bulls were also recorded. The average number of females hand-mated perbull per month varied widely from 5.2 to 21.6. In some cases the bull had to mate up to 52 females in I month. The number of ejaculates for each female service varied between 2 and 3 times. At the proper mating time within 6 to 12 hr after heat detection 86.9% of the buffalo cows Were handmated. Nearly 71.4% of the bulls mount.ed the buffalo cows twice for the first service; 85.7 and 60.6% of the buHR needed only one Lime to ejaculate the second and third serviceR respectively. The stimulus time varied between 29 lind 160 sec for the first service, The average ejaculate volume was 0.75, 0.96 and 1.25 ml for the first, second and third services respectively. The average percentage of progressively motile cells was 57.6% and ranged between 0.0% and 86%. Bull rations differ widely from bull to bull depending on feeds available and not Lo nutritional requirements. Housing and management of buffalo bulls were also studied.